Bridging the generational gap: Exploring youth understanding on ethnobotanical knowledge and its integration in higher education curricula - Rinto, Rinto; Iswari, Retno Sri; Mindyarto, Budi Naini; Saptono, Sigit (Ethnobotany Research and Applications, 2023)
Background: Current ethnobotanical knowledge in Indonesia is declining among the younger generation, particularly university students. Therefore, embedding ethnobotanical knowledge in the formal education curriculum is essential to enhance young awareness of their traditional ecological knowledge. This study aims to analyze ethnobotanical knowledge in undergraduate students as a fundamental step to developing a reliable ethnobotanical learning curriculum in higher education. Methods: This observational exploratory study involved 192 Science Education (SE) and Primary School Teacher Education (PSTE) students in Cirebon District, West Java, Indonesia. An open survey method, employing an online questionnaire, was used to obtain data on ethnobotany knowledge and cognitive competencies. Result: The study results revealed that ethnobotany knowledge in students only reached less than 62.00 points, or moderate to low achievement. Furthermore, cognitive ability related to ethnobotanical knowledge barely got 50% across all levels, except for analytical ability ranging from 59-69%, and creating ability resulted in 0%. Most respondents discovered it challenging to use the concept of ethnobotany to identify new botanical discoveries and the application of ethnobotany in daily life. Furthermore, the respondent understands their weaknesses regarding cognitive perspective and initiate technology-based learning to overcome them. Conclusion: Integrating technology in an ethnobotany-based curriculum can increase identification ability and explore related learning resources to make learning easier for students. Therefore, it is necessary to conduct further studies in developing learning models to increase ethnobotany knowledge through technology. Keywords: ethnobotany, prospective teacher, traditional knowledge, young generation,